On INVOLUTE AND EVOLUTE OF PSEUDONULL AND NULL CURVES IN MINKOWSKI 3-SPACES - Arfah, Arfah (Universitas Cokroaminoto Palopo, 2025)
The aim of this paper is to discuss about the theory of involute and evolute of pseudo-null and null curves in Minkowski space. We apply the Frenet equations of the pseudo-null and null curves in Minkowski 3-space to derive their involutes and the evolutes. Furthermore, some properties of the involutes and evolutes of pseudo-null and null curves in Minkowski 3-space are shown